Video Conference Service Quality Analysis on 802.11g Wlan Network Jaringan Using Quality Of Service (Qos). (Case Study: Zoom App) - EL Rama Janistimewa Nuris Sani; Mohammad Suryawinata (Procedia of Engineering and Life Science, 2021)
Video Conference is an interactive telecommunication technology or system utilizing the internet network so that it is able to interact with audio video with two or more people without considering the distance or different locations, but video conference requires a stable internet network in accordance with the parameters set by Telecommunications and Internet Protocol Harmonization Over Networks (TIPHON) and to determine the quality of video conference can use Quality of Service (QoS). The purpose of this study is to determine delay, throughput, jitter, and packet loss and if someone is doing video conference services on the network, their use can be further enhanced through QoS than other users who only do ordinary internet services (browsing, chatting, etc.) on the network the same network. Here the author uses the Quality of Service (QoS) method as a regulator of internet bandwidth to maximize the use of video conferencing services so that they can run stably when the flow of internet traffic is quite dense. The results of this study are based on the standard TIPHON calculation using the QoS method in testing more or less affect the quality of the video conference service with the evidence in the packet loss recorded at the time of upload and download, mostly touching the 0% figure compared to without using QoS. That way using the help of the QoS method can increase the level of quality and effectiveness in conducting video conference services.